Study and development of the process of production and using of peat-coke bricks at cast iron melting in cupola - N. V. Svidunovich; N. V. Kislov; Ju. P. Bobrov; S. F. Lukashevich (Литьë и металлургия)
In this article there are considered the problem of using of coke waste. There have been proposed to briquette coke waste with peat and use briquettes as the fuel for cupolas heating boilers and furnaces.